2016
DOI: 10.1016/j.jacc.2015.10.077
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Total Cardiovascular Events With Ezetimibe/Simvastatin Post-Acute Coronary Syndrome

Abstract: Lipid-lowering therapy with ezetimibe plus simvastatin improved clinical outcomes. Reductions in total PEP events, driven by reductions in MI and stroke, more than doubled the number of events prevented compared with examining only the first event. These data support continuation of intensive combination lipid-lowering therapy after an initial CV event. (IMProved Reduction of Outcomes: Vytorin Efficacy International Trial [IMPROVE-IT]; NCT00202878).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 187 publications
(84 citation statements)
references
References 23 publications
0
80
0
4
Order By: Relevance
“…Lowering LDL-C levels has been shown to reduce the risk of CVD events in several interventional and epidemiologic studies [1113,3739]; that holds for both statin [40,41] and non-statin therapies [42,43]. The evolocumab CV outcomes trial, Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects With Elevated Risk (FOURIER) [16], demonstrated that the addition of evolocumab to SoC is associated with a reduced incidence of major CVD events.…”
Section: Methodsmentioning
confidence: 99%
“…Lowering LDL-C levels has been shown to reduce the risk of CVD events in several interventional and epidemiologic studies [1113,3739]; that holds for both statin [40,41] and non-statin therapies [42,43]. The evolocumab CV outcomes trial, Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects With Elevated Risk (FOURIER) [16], demonstrated that the addition of evolocumab to SoC is associated with a reduced incidence of major CVD events.…”
Section: Methodsmentioning
confidence: 99%
“…Reductions in total primary endpoint events, driven by reductions in myocardial infarction and stroke, more than doubled the number of events prevented compared with examining only the first event. The number of cardiovascular deaths remained similar between treatment groups [70].…”
Section: Previous Clinical Experience With Simvastatinezetimibe Combimentioning
confidence: 80%
“…5 Prevention of recurrent cardiovascular events can have important implications for cardiovascularrelated healthcare resource use and associated costs, which are expected to rise with the increase in elderly populations, obesity, and diabetes mellitus. 3 We performed a health economic study alongside the IMPROVE-IT trial to examine the impact of simvastatin-ezetimibe combination therapy compared with simvastatin-placebo on the rate of cardiovascular-related hospitalizations and associated costs, both in the overall trial population and in various clinically relevant subgroups.…”
Section: Pokharel Et Al Impact Of Ezetimibe On CV Hospitalization Andmentioning
confidence: 99%